Analysis Of Knowledge Levels With Compliance With Antibiotic Use - Fidyawati Dj Hasihun (Journal of Applied Nursing and Health, 2020)
Infectious disease is still one of the important public health problems, especially in developing countries. Inappropriate use of antibiotics can cause several effects, namely the occurrence of germ or bacterial resistance. Objective To determine whether there is a relationship between the level of knowledge analysis with the compliance of antibiotic use in outpatients in the Gadung District Health Center. Buol The design used in this study is Cross Sectional. The population was all outpatients who received antibiotic treatment. The sample size was 42 respondents using total sampling technique. The independent variable of research is knowledge. The dependent variable is compliance. Data were collected using a questionnaire, then data were analyzed using the rho spearment test with a significance level of α ≤ 0.05. The results showed that almost half of respondents had sufficient knowledge of 18 respondents (42.9%), obedient respondents were 23 respondents (54.8%), the statistical test in this study used the Spearmen's rho test with a <0.05 obtained p = 0,000 where H1 is accepted and H0 is rejected, which means that there is a relationship between the level of knowledge and compliance with the use of antibiotics in outpatients in Gadung District Health Center. Buol There is a relationship between the level of knowledge analysis with adherence to the use of antibiotics in outpatients in the Gadung District Health Center, Buol